Popular Resistance to Legal Authority in the Upper St. Francis District of Quebec: The Megantic Outlaw Affair of 1888-89 - Little, Jack (Labour/Le Travailleur, 1994)
This essay attemps to explain why the Scots Canadians of Québec's upper St. Francis district protected the fugitive, Donald Morrison, against the full force of the law in 1888-89. It rejects the proposition that ethnic tensions were a major factor, arguing instead that Morrison conforms to Eric Hobsbawm's definition of a primitive rebel. With the railway undermining the local subsistence-oriented economy and encouraging families to migrate from the district, the Highland community was facing a survival crisis which it would ultimately lose. The Megantic Outlaw affair therefore represented a final defiant and largely symbolic stand on the part of a tightly-knit rural community succumbing to the forces of industrial capitalism.